ADAMTS13 test and/or PLASMIC clinical score in management of acquired thrombotic thrombocytopenic purpura: a cost‐effective analysis. Issue 11 (23rd June 2017) - Kim, Chong H.; Simmons, Sierra C.; Williams III, Lance A.; Staley, Elizabeth M.; Zheng, X. Long; Pham, Huy P.
Abstract : BACKGROUND: The ADAMTS13 test distinguishes thrombotic thrombocytopenic purpura (TTP) from other thrombotic microangiopathies (TMAs). The PLASMIC score helps determine the pretest probability of ADAMTS13 deficiency. Due to inherent limitations of both tests, and potential adverse effects and cost of unnecessary treatments, we performed a cost‐effectiveness analysis (CEA) investigating the benefits of incorporating an in‐hospital ADAMTS13 test and/or PLASMIC score into our clinical practice. STUDY DESIGN AND METHODS: A CEA model was created to compare four scenarios for patients with TMAs, utilizing either an in‐house or a send‐out ADAMTS13 assay with or without prior risk stratification using PLASMIC scoring. Model variables, including probabilities and costs, were gathered from the medical literature, except for the ADAMTS13 send‐out and in‐house tests, which were obtained from our institutional data. RESULTS: If only the cost is considered, in‐house ADAMTS13 test for patients with intermediate‐ to high‐risk PLASMIC score is the least expensive option ($4, 732/patient). If effectiveness is assessed as measured by the number of averted deaths, send‐out ADAMTS13 test is the most effective. Considering the cost/effectiveness ratio, the in‐house ADAMTS13 test in patients with intermediate‐ to high‐risk PLASMIC score is the best option, followed by the in‐house ADAMTS13 test without the PLASMIC score. CONCLUSIONS: In patients with clinical presentations of TMAs, having an in‐hospital ADAMTS13 test to promptly establish the diagnosis of TTP appears to be cost‐effective. Utilizing the PLASMIC score further increases the cost‐effectiveness of the in‐house ADAMTS13 test. Our findings indicate the benefit of having a rapid and reliable in‐house ADAMTS13 test, especially in the tertiary medical center.